A COMPREHENSIVE APPROACH TO ASSESSING MARKET DEMAND FOR HIGH-TECH EQUIPMENT - Alimov, Otabek Sayfutdinovich (THE INNOVATION ECONOMY, 2026)
The scientific article is devoted to a comprehensive assessment of market demand for science-intensive technological equipment in the industrial sectors of the of Uzbekistan, based on the analysis of existing and planned regional development investment programs. The study is grounded in systemic, institutional, comparative-analytical, platform-ecosystem, and economic-mathematical approaches. Key technological gaps, structural shifts, and sectoral priorities that determine the demand for equipment have been identified. A mapping of regional investment projects has been conducted to aggregate demand and identify the need for critically important equipment. The results of the study form a methodological foundation for the high-tech services provided by modern scientific and production centers (SPCs), aimed at accelerating the localization of import-substituting products.